PENGARUH KUALITAS SUMBER DAYA MANUSIA, KOMITMEN ORGANISASI DAN SISTEM PENGENDALIAN INTERN TERHADAP KEBERHASILAN SAP BERBASIS AKRUAL DI OPD KABUPATEN MALANG - Tri wulandari; Nur Hidayati; Muhammad Cholid Mawardi (Universitas Islam Malang, 2018)
ABSTRACTGovernment Accounting Standards aims to provide basic guidance in thepreparation and presentation of government financial reports both central andlocal governments. While accrual based government accounting standards beganto be applied in Indonesia based on Government Regulation No. 71 of 2010. Thistype of research uses a quantitative approach. The location of the research is atthe OPD office of Malang Regency, the samples taken are the governmentemployees in the OPD office of Malang Regency. Data collection techniques usedquestionnaire method, the analysis tool used is multiple linear regression. Theresults of this study indicate that the variable quality of human resources,organizational commitment, and internal control system significantly influencethe success of government accounting standards based on accruals in OPDMalang Regency.Keywords: quality of human resources, organizational commitment, internalcontrol system and accrual-based SAP success.